Mandibular Third Molar Impaction: Review of Literature and a Proposal of a Classification - Gintaras Juodzbalys; Povilas Daugela (eJournal of Oral Maxillofacial Research)
Objectives: The purpose of present article was to review impacted mandibular third molar aetiology, clinical anatomy, radiologic examination, surgical treatment and possible complications, as well as to create new mandibular third molar impaction and extraction difficulty degree classification based on anatomical and radiologic findings and literature review results.Material and Methods: Literature was selected through a search of PubMed, Embase and Cochrane electronic databases. The keywords used for search were mandibular third molar, impacted mandibular third molar, inferior alveolar nerve injury third molar, lingual nerve injury third molar. The search was restricted to English language articles, published from 1976 to April 2013. Additionally, a manual search in the major anatomy and oral surgery journals and books was performed. The publications there selected by including clinical and human anatomy studies.Results: In total 73 literature sources were obtained and reviewed. Impacted mandibular third molar aetiology, clinical anatomy, radiographic examination, surgical extraction of and possible complications, classifications and risk factors were discussed. New mandibular third molar impaction and extraction difficulty degree classification based on anatomical and radiologic findings and literature review results was proposed. Conclusions: The classification proposed here based on anatomical and radiological impacted mandibular third molar features is promising to be a helpful tool for impacted tooth assessment as well as for planning for surgical operation. Further clinical studies should be conducted for new classification validation and reliability evaluation.